Cryopreservation of Low Number of Human Spermatozoa; Which is Better: Vapor Phase or Direct Submerging in Liquid Nitrogen?. (3rd April 2019) - Hosseini, Akram; Khalili, Mohammad Ali; Talebi, Ali Reza; Agha-Rahimi, Azam; Ghasemi-Esmailabad, Saeed; Woodward, Bryan; Yari, Nahid
Abstract: Cryopreservation and subsequent survival of semen samples with low numbers of human spermatozoa in assisted reproductive technology (ART) facilities can be challenging. The aim of this study was to compare the quality of warmed human spermatozoa following vitrification using direct submerging (DS) in liquid nitrogen (LN2 ) or with LN2 vapour (V). Normozoospermic ejaculates were prepared by the swim-up technique and the motile sperm fraction was divided into three groups: (i) fresh (control); (ii) DS methods in LN2 (DS Group); or (iii) cryopreserved in V (Group V). Cryopreservation was performed in a small volume using a Cryotech device. After warming, sperm parameters (motility, viability, acrosome, DNA fragmentation and chromatin integrity) were assessed using cytochemical assays. Progressive motility, viability, chromatin integrity and DNA fragmentation differed significantly after warming when compared with the control. Sperm progressive motility and total motility rates were significantly higher in the DS Group compared to Group V. However, normal morphology, acrosome integrity and DNA damage were not significantly different between two groups. Also, sperm chromatin condensation using chromomycin-A3 (CMA3) and Aniline Blue (AB) staining showed fewer alterations in the DS Group compared to Group V. The rates of spermatozoa with an intact acrosome decreased significantly after thawing from 81.30 ± 6.76% to 68.84 ± 14.70% in the DS Group and to 60.92 ± 8.06% in Group V. Cryopreservation of a small number of spermatozoa with the DS method showed superior outcomes with regard to motility, viability and chromatin configuration.